Characterization of mechanical behaviour of healthy and injured human incus by eigenfrequency evaluation. (March 2020) - Gyliene, Virginija; Gylys, Giedrius; Lipinski, Pawel; Wronski, Sebastian; Tarasiuk, Jacek; Baldit, Adrien; Rahouadj, Rachid; Eidukynas, Valdas; Kraptavičiūte, Neringa
The usage of finite element method techniques gives a possibility to replace time-consuming experiments or imitate physical process in the ear by numerical simulation. Especially, the research of spatial motion of ossicular chain in the middle ear is of high interest for the oto-surgeons and engineers. It is known that the most affected bone from the ossicular chain is the incus. After the cholesteatoma operation and tympanoplasty, the affected incus is removed or sacrificed; thus, the possibility of transducing noise lays on the stapes, new titanium or other material prosthesis. In this case, the affected incus was removed because of the cholesteatoma that was lying in front of it in the tympanic cavity. The removed incus with the affected long process passed micro–computed tomography. The computer-aided design systems allowed redesigning a 'healthy' incus with an intact long process. In this way, it was possible to evaluate the influence of damaged long process of incus in the vibrational analysis. This article analyses the problems of mechanical behaviour of injured and healthy human incus. The numerical simulation has demonstrated that the features of healthy incus and analysed injured incus do not differ significantly, especially at low (about 500 Hz) frequencies. It explains why there is no impact of cholesteatoma on hearing for a long time in the audiogram.